Dose, duration and strain of bacillus Calmette–Guerin in the treatment of nonmuscle invasive bladder cancer: Meta-analysis of randomized clinical trials. Issue 42 (October 2017) - Quan, Yongjun; Jeong, Chang Wook; Kwak, Cheol; Kim, Hyeon Hoe; Kim, Hyung Suk; Ku, Ja Hyeon
Abstract: Background: Intravesical bacillus Calmette–Guerin (BCG) instillation is widely used as an adjuvant therapy after transurethral resection of bladder tumor (TURBT) in patients with intermediate- and high-risk nonmuscle invasive bladder cancer (NMIBC). However, the effective dose, duration, and strain of BCG have not yet been clearly determined. We aimed to elucidate the relationship between dose, duration, and strain of BCG and clinical outcomes in NMIBC patients treated with TURBT. Methods: We conducted a literature search in Embase, Scopus, and PubMed databases for all relevant articles published up to October 2016 in accordance with the Preferred Reporting Items for Systematic Review and Meta-analysis guidelines. The relative risks of clinical outcomes, including recurrence, progression, cancer-specific mortality, and all-cause mortality according to dose (standard vs low), duration (induction vs maintenance), and strain of BCG were presented as the pooled risk ratio (RR) and 95% confidence interval (CI). Results: Nineteen studies meeting the inclusion criteria were finally selected in this meta-analysis. The risk of recurrence was significantly highly observed in case of low-dose BCG (RR, 1.17; 95% CI 1.06–1.30) and induction BCG (RR, 1.33; 95% CI 1.17–1.50) only group without heterogeneity among the included studies. Although there were no significant differences between dose or duration and other clinical outcomes. On direct comparison in each study comparing BCG strains, the Tice stain showed a relatively high probability of recurrence compared with the Connaught (RR, 1.29; 95% CI 1.01–1.64) and RIVM (RR, 2.04, 95% CI 1.28–3.25) strains. Funnel plot testing revealed no significant publication bias. Conclusion: The use of standard dose and maintenance BCG instillation may be effective to reduce recurrence rate after TURBT for NMIBC. Further large scale, well-designed, and prospective studies, with stratification of the patients into risk group at randomization, will be required to determine the optimal guideline of BCG use to improve clinical outcomes in NMIBC. Abstract : Supplemental Digital Content is available in the text